Impacts of Carbon Pricing on Developing Economies - Koh, Jane; Johari, Shazali; Shuib, Ahmad; Matthew, Nitanan Koshy; Siow, May Ling (International Journal of Energy Economics and Policy, 2021)
Carbon pricing is widely recognized as an effective policy instrument for climate change mitigation. Carbon pricing have been imposed in 39 developed countries and eight middle-income countries. Eight more middle-income countries are considering its implementation. As experiences from industrialized countries may not be relevant to developing countries, this literature review fills a knowledge gap by collating the impacts of carbon pricing in developing economies to facilitate cross-learning. Some developing countries still have distortionary subsidies in place, while others are going through environmental fiscal reforms to nudge their societies and economies towards greenhouse gases emission reduction. Various studies demonstrated that safeguards introduced with carbon pricing could help firms to transition while maintaining the motivation to innovate to stay competitive. At the household level, given different energy consumption patterns, carbon pricing in developing economies is not necessarily regressive, especially for rural population. Aggregate impacts to employment rate and gross domestic product change over time as the economy restructures towards decarbonization. A well-designed carbon pricing policy package with revenue recycling mechanisms tailored to the socioeconomic circumstances of the country could achieve multiple dividends of economic growth, increased employment, improved equality, national debt reduction or accomplishment of other sustainable development goals. Keywords: Carbon tax, emissions trading system, developing countries, competitiveness, distributional impact, economic impact. JEL Classifications: H23, Q56, Q58 DOI: https://doi.org/10.32479/ijeep.11201